2017
DOI: 10.1111/ijfs.13358
|View full text |Cite
|
Sign up to set email alerts
|

Combined use of cocoa dietary fibre and steviol glycosides in low‐calorie muffins production

Abstract: Summary Today, consumers are more conscious about nutrition and food products with health benefits. In this study, partial sucrose replacement (20%) with steviol glycosides derived from Stevia Rebaudiana and total replacement of cocoa powder with cocoa fibre preparation in muffins were conducted. There were three levels of dietary fibre addition – 3%, 6% and 12%. Physical analysis of texture, colour, cooking yield and porosity was conducted. Moreover, chemical analysis of total dietary fibre and total phenol c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 36 publications
0
12
1
Order By: Relevance
“…On the other hand, stevia was used as an alternative for synthetic or powerful sweetener, which indeed reduces the growth of oral bacteria and species specific odour. It has been proved to contain sweet diterpene and acylated glycoside (Karp et al 2017) which gives sweetening property. This natural sweetener has the ability to maintain glucose level in diabetic's patients and scientifically proven to be nontoxic (Karp et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, stevia was used as an alternative for synthetic or powerful sweetener, which indeed reduces the growth of oral bacteria and species specific odour. It has been proved to contain sweet diterpene and acylated glycoside (Karp et al 2017) which gives sweetening property. This natural sweetener has the ability to maintain glucose level in diabetic's patients and scientifically proven to be nontoxic (Karp et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Dietary fibre is also considered as a technologically beneficial ingredient in food processing as it improves both physicochemical and sensory properties such as cooking yield, water holding capacity and gel forming capacity (Elleuch et al ., ). It has been reported that dietary fibre could be incorporated into food products including bakery products, beverages, dairy and meat products (Buriti et al ., ; Choi et al ., ; Liutkevičius et al ., ; Karp et al ., ) to improve the product quality and add value to the food industry.…”
Section: Introductionmentioning
confidence: 99%
“…Other parts including the pods and shells are usually discarded. Despite to be thrown, Karp, Wyrwisz, Kurek, and Wierzbicka (2017) showed that cocoa shells contain fibers that can be used in the formulation of low-calorie foods. Cocoa pods can be used to remove pollutants from waters and wastewaters (Cruz et al, 2012).…”
Section: Introductionmentioning
confidence: 99%